2017
DOI: 10.1002/jca.21529
|View full text |Cite
|
Sign up to set email alerts
|

Plasma exchange in the intensive care unit: Technical aspects and complications

Abstract: Plasma exchange is a relatively safe and generally well-tolerated procedure in the ICU setting. Most adverse events are unpredictable and related to minor allergic reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
53
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(72 citation statements)
references
References 25 publications
(42 reference statements)
5
53
1
Order By: Relevance
“…Almost all patients in our study were treated with immunosuppressors combined with plasmapheresis (70%). Other ICU studies showed similar percentages of adjuvant immunosuppressive drugs use (76%--82%) 8,11,13 . The most used immunosuppressants were steroids, intravenous immunoglobulin, mycophenolate mofetil and azathioprine.…”
Section: Complications and Therapy Outcomesmentioning
confidence: 59%
See 3 more Smart Citations
“…Almost all patients in our study were treated with immunosuppressors combined with plasmapheresis (70%). Other ICU studies showed similar percentages of adjuvant immunosuppressive drugs use (76%--82%) 8,11,13 . The most used immunosuppressants were steroids, intravenous immunoglobulin, mycophenolate mofetil and azathioprine.…”
Section: Complications and Therapy Outcomesmentioning
confidence: 59%
“…In 60% it was necessary to start at least one organ support (mechanical ventilation -50%, RRT -37.5% or vasopressor therapy -12.5%) which is in accordance with a Spanish study of 24 ICU patients submitted to plasmapheresis where 62.5% needed organ support 14 . In contrast, Lemaire et al 8 and Benítez et al 14 showed a different incidence of organ support with 14 -27.8% patients requiring vasopressor therapy, 22 -31.6% mechanical ventilation, and 24 -26.3% patients requiring RRT. These differences are probably related to the underlying diseases, since our study included more patients with myasthenia gravis (5 vs. none 8,13 ) which may explain the higher need of mechanical ventilation.…”
Section: Complications and Therapy Outcomesmentioning
confidence: 92%
See 2 more Smart Citations
“…Close hemodynamic monitoring and frequent evaluation of new symptoms (ie, shortness of breath, lightheadedness) in an intensive care setting are recommended. One of the most significant studies on TPE in the intensive care unit evaluated 260 TPE procedures performed in 50 patients, and the researchers reported that around 1.1% of cases developed life‐threatening complications and 26.9% exhibited non–life‐threatening complications …”
Section: Cases and Discussionmentioning
confidence: 99%